PENGARUH SUSTAINABILITY REPORTING TERHADAP NILAI PERUSAHAAN DENGAN INVESTMENT OPPORTUNITY SET SEBAGAI VARIABEL MODERATING - Normasari Dwi Purwanti; Maslichah Maslichah; M. Cholid Mawardi (e_Jurnal Ilmiah Riset Akuntansi, 2019)
AbstractThis research was conducted to determine the effect of Sustainability Reporting on Corporate Values with Investment Opportunity Set as a Moderating Variable. This study uses secondary data in the form of annual reports and ongoing reports of the company. The population of this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2014-2017 period. By using a purposive sampling technique, there are 31 companies that meet the specified criteria 124 data during the study period from 2014-2017. Analysis of this research data using Moderate Regression Analysis (MRA). This study shows that Sustainability Reporting and Investment Opportunity Set have a significant positive effect on Corporate Value, while the results of the Moderate Regression Analysis (MRA) test show that the Investment Opportunity Set can moderate the effect of Sustainability Reporting on Firm Value.Keywords: Sustainability Reporting, Company Value, Investment Opportunity Set.